CHEMICAL TYPOMORPHISM OF THE SURFACE OF PYRITE CRYSTALS OF GOLD ORE DEPOSITS - Tauson V.L.; Kravtsova R.G.; Grebenshchikova V.I. (My University, 2004)
The specific features of natural systems inspire certain optimism, since they represent heterogeneous multisystems with a great number of phase and the respective phase boundaries. This implies that the so-called nonautonomous surface phases, which can exist only in association with bulk phases, can be formed and retained over geological time. According to the classic interpretation, these phases represent layers of a finite thickness that are formed between two contacting bulk phases and characterized by excess partial thermodynamic properties as a result of the presence of an interface between the phases. As has been shown in our recent experimental works, thenonautonomous phases are formed not only at the boundaries of bulk phases, but also as a result of the interaction of components of a medium with the free surfaces of minerals. These phases can be buried in the oxidized surface layer adn bear information on the history pf physicochemical processes and the residence of certain chemical elements at the surface. The present communication substantiates such a possibility based on the study of natural material.